Virtual reality commissioning in production systems preparation - Dahl, M.; Albo, A.; Eriksson, J.; Pettersson, J.; Falkman, P. (2017 22nd IEEE International Conference on Emerging Technologies and Factory Automation (ETFA), 2017)
Virtual commissioning (VC) is a method used to virtually visualize and test production systems, control logic and material flows. The focus of this paper is to further extend this concept using Virtual Reality (VR). The introduction of VR in VC enhances the concept by adding a more realistic visualization and movement tracking which extends the possibilities of its validation. The changes to the validation aspect are mainly due to the fact that it is now possible to interact with the running virtual production in a realistic and intuitive way. The interaction gives designers and operators a new possibility to go from being observers to actors in the design phase. They are now able to validate the production system, test security protocols and validate the human interaction with the system, using VR.